Reliability Analysis of Horizontal Curves Using Geometric Design Consistency Assessment Criterion - Hossein Saedi; Ali Abdi Kordani; Seyed Mohsen Hosseinian (Journal of Advanced Transportation)
Road accidents have always been one of the important reasons for fatalities and financial losses. Since road accidents on rural highways cause more serious injuries than those on urban highways, providing a suitable method to increase safety in the curves can be a significant contributor to preventing these damages. Although speed is one of the most important variables affecting highway safety, numerous studies have been performed on the reliability analysis of horizontal curves without taking the speed variable into account. The aim of this research is reliability (probability of noncompliance) assessment in the horizontal curve design using geometric design consistency criteria. The radius, superelevation, and operating speed of 19 horizontal curves were collected by field research on the Mashhad-Torbat Heydarieh highway in Iran. Three different approaches were defined based on the geometric design consistency criterion of a single horizontal curve, and consecutively, the probability of noncompliance was calculated using these approaches. According to the obtained results, this study showed that radius enhancement increases the probability of noncompliance and the consistency level of the geometric design. Finally, the high values of the probability of noncompliance (failure) indicate that the geometric design guidelines need calibration in the design of horizontal curves, especially for higher radii.